Effects of Tai Chi on insomnia in elderly people with chronic non-specific low back pain: A study protocol for a randomized controlled trial - Zhang, Feng; Zhang, Boran; Wang, Xiaotong; Huang, Chang; Hu, Boyi (Frontiers in Psychology, 2023)
Introduction: Chronic nonspecific low back pain (CNLBP) is a complex disorder by pain, dysfunction, sleep disturbance, anxiety, depression, causing quality of life impairments. Previous studies showed that Tai Chi had effects on chronic low back pain, however, there is lacking evidence on sleep. The trial will evaluate Tai Chi in the treatment of insomnia in elderly people with CNLBP. Methods: A randomized, controlled, open-label trial will be conducted. Participants (n=122) will be recruited from the Hospital of Chengdu University of Traditional Chinese Medicine, Qing Yang District University for the Elderly, and Ci Tang Street Community. Participants will be randomly allocated to Tai Chi group (n=61) and Control group (n=61). The Tai Chi group will receive Yang style 24-form Tai Chi program for 8 weeks. The Control group had a waiting time of 8 weeks, followed by 8 weeks of Tai Chi practice. The primary outcomes will be sleep and pain intensity. The secondary outcomes include quality of pain, range of motion, physical performance, social support and quality of life. The adverse events and attendance rate will be reported in our study. Clinical trial registration: ChiCTR2200064977 Keywords: Tai Chi, insomnia, chronic nonspecific low back pain, randomized controlled trial，elderly people